2001
DOI: 10.1021/la010746q
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and in Situ FTIR Spectroscopic Investigation on the Electrochemical Transformation of 4-Aminothiophenol on a Gold Electrode in Neutral Solution

Abstract: The electrochemical transformation of the self-assembled monolayer of 4-aminothiophenol (4-ATP) has been studied in neutral solution by means of electrochemical and in situ FTIR measurements, and the results are compared with those in acidic solution. The electrochemical transformation in neutral solution results in the formation of a surface-confined aniline dimer, 4‘-mercapto-N-phenylquinone diimine as in the case of acidic solution. The redox peak corresponding to the aniline dimer shifts by −56 mV while in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 68 publications
5
77
0
Order By: Relevance
“…Among them, SAMs based on aromatic thiols have been vastly studied [13,14]. The formation of organic monolayers by self-assembly is directed by a specific interaction between a terminal functional group and the surface, in this case, the bond formed between the thiol sulphur and the metal.…”
mentioning
confidence: 99%
“…Among them, SAMs based on aromatic thiols have been vastly studied [13,14]. The formation of organic monolayers by self-assembly is directed by a specific interaction between a terminal functional group and the surface, in this case, the bond formed between the thiol sulphur and the metal.…”
mentioning
confidence: 99%
“…The height of peak A and B decreases and the height of peak C increases with the pH value of the solution increase [22]. Contradictory information could be found in References, for example [22] mentioned peak B and C could disappear at solution pH > 6 while [24] said both Peak B and C could be observed even when solution pH > 9. In our experiment, we could only observe peak C (see Figure 2).…”
Section: Instrumentation and Proceduresmentioning
confidence: 94%
“…Although the extent of decrease in limiting current is different for different 4-ATP SAMs modified nanometer-sized Au electrode, the phenomenon is reproducible. According to References [22][23][24], 4-ATP molecules on the electrode are electrochemically dimerized to form 4'-mercapto-N-phenylquinone diimine (NPQD). It seems that the entire electrode is covered by NPQD molecules because the current of the oxidation of hydrazine on the modified electrode, which is believed to be an inner-sphere electron transfer reaction [28], is very small compared with the same reaction on the electrode before modification (see Figure 3c).…”
Section: àmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation suggested that the electron transfer rate of the p-ATD film decreases when the deposition cycles increase. We calculated the surface coverage of the polymer film by integrating the area under the anodic wave [29]. A surface coverage of 2.12 × 10 −10 mol cm −2 was obtained for the p-ATD film deposited by 15 cycles.…”
Section: Electrochemical Behavior Of P-atd Filmmentioning
confidence: 99%